Enterprise Arrears in Russia : Causes and Policy Options - Bigman, David (IMF Working Papers; Working Paper ;, 1993)
This paper examines the causes of the large buildup of enterprise arrears in Russia during 1992, and evaluates policy options to deal with them. Noting the experience of. Eastern European countries, the paper emphasizes that the settlement of arrears through wholesale extension of credit would only achieve a temporary reduction of arrears while inviting moral hazard problems and creating expectations of future bailouts. Instead, emphasis should be placed on measures that instill financial discipline and promote necessary structural changes. These measures should be supported by adequate legislation, effective supervision, and credible sanctions against defaulting enterprises and their managers.